PERANCANGAN AWAL SCALE MODEL GLIDER STTA-25-02_SAILPLANE - Firmansyah, Hendrix Novianto; Junaidin, Buyung; Mauliadi, M. Fatha (Sekolah Tinggi Teknologi Adisutjipto, 2016)
The knowledge and experience in aircraft design, especially for glider or sailplane are very important to have. Today, process of designing glider developed so rapidly, especially in America and Europe, one of the significant achievement is the performance aspect of glider. For example, the German-built Eta has a wingspan 30.78 m, aspect ratio 51 and wing loading 50.97 kg/m2, with glide angle of 0.8 degree and 3 km altitude, the glider able to fly 213 km in horizontal direction. Therefore, as the first step to understand the preliminary design of glider, it is important to start with designing a scale model glider STTA-25-02_Sailplane. The goals of this design are to get geometry and configuration of the glider, to obtained stability of glider and to gain performance data that meet with design requirements and objectives data (DR&O). The conclusions from the preliminary design of scale model glider STTA-25-02_Sailplane are the geometry and configuration are good, for example the achivement in performance, the minimum sink rate 0.52 m/s, the glide ratio more than 20 at a cruising speed over 13 m/s, stall speed 11.45 m/s at angle of attack 0 degree. In addition glider STTA-25-02_Sailplane has static and dynamic stability, the static stability condition is indicated by the value of trim angle is positive 1 degree, curve of Cma and Clfi has negative slope, Cnfi curve has positive slope. The dynamic stability condition is indicated by the eigen value for each mode o f movement are negative except on phugoid and spiral mode, eigen value for short period -5.7681 ± 7.0010, phugoid 0.0403 ± 1.1136, rool damping -32.6243, dutch roll -1.0468 ± 3.4891 and spiral 0.1467. Positive eigen value on phugoid and spiral mode can be solved by adding a control parameter of the controlsurfaces.